Stock Valuation, Price Earning Ratios, and Firm Performance - Osman, Suzana Idayu Wati (2010)
The primary objective of this thesis is to reassess the functional form of one of the most popular capital market ratios i.e. the Price Earnings Ratio (PER). The PER is a tool which is widely used by the investors and financial analysts as a stock valuation guide. Inferences made from PER usually affect the investment decision-making process when valuing stock returns. Thus, the key limitations of the PER must be addressed in order to avoid ambiguous interpretation and generalizations of empirical findings. Within a geometric framework, using the criteria of symmetry and proportionality, this thesis illustrates a fundamental characteristic feature of PER being heavy on its denominator (Earnings) as compared to the numerator (Price). The identification of the underlying functional relationship between the numerator and denominator reveals the non-proportionality and non-symmetrical issues which in turn distorts the measurement of stock performance that contributes to inaccurate measure of the estimated value of the firms. Using PER as a representative example, this thesis introduces new measures to stock valuation, namely the Geometric Boundary Indicator (GBI), the Benchmark Geometric Boundary Indicator (BGBI), and the Geometric Share Approach (GSA). Within the GSA framework, a new complimentary measure of stock valuation; the value ratio index ( SPER ), is then proposed. This SPER is free from the asymmetric and non-proportionality characteristics of PER. This thesis adopts some recent and significant contributions made to the international trade literature in using ‘geometrical approach’ to address the weaknesses of ratios; where compatible stock valuation frameworks were developed and constructed from which complementary measures of stock performance are derived and their performances are numerically illustrated. The applicability and usefulness of the newly proposed approaches were then subsequently tested on the data. A comparative performance analysis of the traditional PER and the new proposed measures were empirically tested. Among the significant contributions of this thesis are 1) Comparatively, the results have successfully demonstrated that the new approaches performed better, 2) the findings of this research bring new and strong implications to the use of PER as indicators of stock valuation and 3) this thesis has significantly introduced new stock valuation techniques to the existing literature.